You are a badass : how to stop doubting your greatness and start living an awesome life - Sincero, Jen (Philadelphia : Running Press, 2023)
A motivational guide encouraging readers to identify self-sabotaging beliefs and behaviors to create a life they love.
Includes reading group guide.
Keywords: Self-actualization (Psychology); Motivation (Psychology); Conduct of life